Influence of Air Annealing and Gamma Ray Irradiation on the Optical Properties of Cl16FePc Thin Films - Raji Koshy; C. S. Menon (E-Journal of Chemistry)
Metal phthalocyanines are one of the most promising candidates to be used in the fabrication of such devices. Among various phthalocyanines, Iron Hexadecachloro Phthalocyanine (Cl16FePc) has received less attention. Basic characteristics of Cl16FePc are not reported in literature. Hexadecacholoro phthalocyanines have attracted interest as possible n-type organic semiconductor with high electron mobility and good stability characteristics. In the present work we investigate the optical band gap of the Cl16FePc thin films from the optical absorption spectrum as a function of air annealing temperatures and their suitability for the fabrication of molecular electronic devices. Some optical properties of the samples were studied as a function of γ-radiation doses also. Optical transition is found to be of direct type and optical band gaps are determined by analyzing the absorption spectrum. Vacuum sublimed thin films of Iron hexadecachloro phthalocyanine were prepared at room temperature onto glass substrates at a base pressure of 10-5 Torr on precleaned glass substrates using Hind Hivac 12A4 coating plant. The optical energy band gap Eg were calculated. The mechanism of optical absorption follow the rule of direct transition. In the present paper we also report refractive index, real and imaginary parts of optical dielectric constant etc. from the reflectance measurements.